2020
DOI: 10.3390/ani10071154
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Alleviates Mouse Colitis by Regulating Gut Microbiota Dysbiosis

Abstract: Inflammatory bowel disease (IBD) develops as a result of complicated interactions between genetic susceptibility, excessive innate immunity, and environmental factors, which are mainly related to the gut microbiota. The present study aimed to elucidate the protective effects and underlying mechanisms of a short-chain fatty acid salt, sodium butyrate, on colonic inflammation induced by dextran sulfate sodium (DSS) in mice. Pretreatment with sodium butyrate attenuated colitis, as demonstrated by the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…Due to colonic edema, the weight increased, the length shortened, and the ratio of colonic weight to colonic length was higher in the DSS model mice than that in normal mice. 1 , 19 , 20 The colonic length was significantly longer in the LA-G than in the DSS-G, and the ratio of colonic weight/length was smaller in the LA-G than in the DSS-G. The pathological sections of the colon tissue further showed that LA-XY27 treatment significantly reduced the infiltration and proliferation of lymphocytes caused by inflammation, which preliminarily proved the anti-inflammatory effect of LA-XY27 on DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 80%
“…Due to colonic edema, the weight increased, the length shortened, and the ratio of colonic weight to colonic length was higher in the DSS model mice than that in normal mice. 1 , 19 , 20 The colonic length was significantly longer in the LA-G than in the DSS-G, and the ratio of colonic weight/length was smaller in the LA-G than in the DSS-G. The pathological sections of the colon tissue further showed that LA-XY27 treatment significantly reduced the infiltration and proliferation of lymphocytes caused by inflammation, which preliminarily proved the anti-inflammatory effect of LA-XY27 on DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 80%
“…Mechanistically, SCFAs may promote the integrity of the intestinal epithelial barrier by increasing the synthesis of mucins in the mucosal layer [ 68 ] and of TJ proteins in the epithelial monolayer [ 69 , 70 ], and thus, contribute to the remission of colitis. In addition, SCFAs attenuate colitis in mice by restoring the balance of gut microbial dysbiosis [ 71 , 72 ]. In this study, feeding B. vulgatus 7K1 to mice protected the TJs of their intestinal epithelial cells ( Figure 7 ), but did not restore the balance of the gut microbial dysbiosis caused by DSS ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, butyrate does modulate intestinal inflammation, and dysbiosis in IBD may contribute to disease severity [ 70 , 71 ]. Butyrate mediates intestinal inflammation predominantly through binding of free fatty acid receptors (FFAR), a family of GPCR present on the epithelial cell membrane [ 72 , 73 , 74 ].…”
Section: Butyrate As An Immunomodulator In the Intestine And Beyondmentioning
confidence: 99%